Trans-National Migration For Human Development The Dhivehi Diaspora in Kerala - Sheeja Beevi H
The article examines the human development context of Dhivehi Diaspora in Kerala. The „Dhivehi Diaspora‟ actually belongs to the community of the people living in Maldives, are those who speak the language Dhivehi. The Maldives generally known as the Maldives Islands is an island nation situated in the Indian Ocean. A large number of people from Maldives migrated to India, especially to Kerala. The main purpose behind this migration is medical services, education and training, business purposes and official trips or holidaying. Majority of the Dhivehi people came to India for various purposes, most commonly for holiday purpose which include medical checkups and treatments. In Kerala, they have got ample opportunities for health services and education for low cost.